THE EFFECTS OF LAPROL-604 EXPOSURE OF PREGNANT RATS ON THE KIDNEYS OF THEIR PROGENY - T.M. Popova (Проблеми екології та медицини)
The production of surfactants has been regarded as an important indicator of high-tech chemical technology industry all over the countries. It has become the world's chemical industry competitive focus. There is no doubt that the expanding of surfactants application field leads to the increase of its consumption. Eventually, the harm to the environment will be more serious. Therefore, the researches of affects of surfactants on living organisms are very important. The aim of this study was to study the influence of Laprol-604 on enzymatic system of kidney. Kidney’s peculiarities of rat pups were analyzed. Laprol-604 was introduced during pregnancy of Wistar rats. It has been found that there is a statistically significant disturbance of metabolic parameters of kidneys. The exposure to Laprol-604 to pregnant rats led to the appearance of kidney-specific enzyme such as L-arginine: glycine amidinotransferase in blood serum of the offsprings. While the activities of alanine aminotransferase and aldolase were increased, the activity of isocitrate dehydrogenase was decreased in the kidney homogenates of progeny. These changes may be associated with mitochondrial dysfunction that is evidenced by decreasing concentration of adenosine triphosphate. The concentration of proteins was reduced in the kidney homogenates. With the help of chemiluminescent method it was found that such biochemical changes occurred during the activation of free-radical oxidation. The findings revealed the appearance of damages in the kidneys followed by an accelerated rate of free-radical oxidation.